Avaliação experimental do crescimento da comunidade fitoplanctônica do reservatório João Leite em diferentes condições de luz e nutrientes - Pina, Rafaela Wolff de (2013)
Human activities of natural resources exploration can have negative impacts on lakes and reservoirs. The increase in the amount of nitrogen and phosphorus in water cause deterioration in the water quality and eutrophication. Eutrophication by algae and cyanobacteria may hinder the use of water for several purposes. João Leite’s reservoir, located in the state of Goiás, is an important water resource for the public supply; approximately, 2.300.000 inhabitants are in need of its water. The present work aimed to study the dynamics of variation of a phytoplankton community in João Leite’s reservoir by a bioreactors board studies in order to evaluate the population growth of phytoplankton in different conditions of light and nutrients. The experiments were performed in nine bioreactors with controlled light conditions (22 μmol de fótons.m-2 .s-1, 44 μmol de fótons.m-2 .s-1,, 67 μmol de fótons.m-2 .s-1) and nutrients (N / P = 10) (N / P = 16) and (N / P = 20) and according with a factorial experimental design with two factors at three levels (3 Meters). The bioreactors were submitted to a photoperiod of 12/12 hours and kept at a temperature of 25 ± 2 ° C. The natural water samples were collected in 5 sampling campaigns in the months of April, May, June and July 2013 from João Leite’s reservoir and monitored for five consecutive days in the laboratory. The results showed a significant positive correlation between light and nutrients on the growth of algae and cyanobacteria. A principal component analysis (PCA) indicated light intensity and nitrate as the factors that most influenced the increase of phytoplankton density. The paired t-test and Tukey tests showed that the effect of light, however, was more significant than the effect of nutrients. The growth of algae and cyanobacteria were modeled as logistic model that adjusted well to the data with R ² value ranging between 0.80 and 0.99. The laboratory experiment corroborated the data of seasonal variations in the reservoir, in which occurred as the increase of algae and cyanobacteria density as was the increase in nitrate concentration and light intensity.